THE RELATION OF FAMILY SUPPORT FOR ADHERENCE OAT TREATMENT AT POLIKLINIK PARU RSUD KABUPATEN TANGERANG - oktaviani, elih elih (Journal of Smart Nursing and Health Science, 2025)
Tuberculosis is an infectious disease that is a public health problem in the world. Tuberculosis is still a threat due to its complexity and high death rate resulting from non-adherence with treatment. The aim of the research was to determine the relationship between family support and adherence to OAT treatment at the Lung Polyclinic of RSUD Kabupaten Tangerang. The research methodology used a descriptive quantitative type with a cross sectional approach involving 89 respondents from Tuberculosis patients and their families who visited the Pulmonary Polyclinic at the Tangerang District Hospital. The sampling technique uses purposive sampling. The research was carried out in November 2022. The research instrument used the Morisky Medication Adherence Scale questionnaire which had been adapted into Indonesian. The results of research from 89 respondents who were tuberculosis patients showed that 53 respondents (59.6%) received good family support and 67 respondents (75.3%) had tuberculosis patients who were compliant with OAT treatment. The results of bivariate analysis using chisquare showed a p-value of 0.036, which means there is a significant relationship between family support and OAT treatment compliance in the Lung Clinic of Tangerang District Hospital (p-value < 0.05). Family support is an important aspect to maintain and increase patient compliance undergoing tuberculosis treatment. Suggestions from the research results are that it is hoped that nurses and health workers involved in tuberculosis treatment can facilitate families and patients to complete treatment and be accompanied by family as supervisors of taking medication at each visit.